Матеріальні носії секретної інформації: поняття, види і порядок зберігання під час кримінального провадження - Ковальчук, С. О.; Koval'chuk, S.; Крет, Г. Р.; Kret, G. (My University, 2013)
The article is dedicated to analyzing the concept of material transmitters of secret information, for which proposed to lay out the normative definition in the new edition. Types of material transmitters of secret information are determined and claims of secrecy regarding the storage of them during the preliminary investigation and prosecution of criminal proceeding are investigated.
Ковальчук С. О., Крет Г. Р. Матеріальні носії секретної інформації: поняття, види і порядок зберігання під час кримінального провадження / С. О. Ковальчук, Г. Р. Крет // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 410-419.
Keywords: кримінальне провадження; державна таємниця; матеріальні носії секретної інформації; уголовное производство; государственная тайна; материальные носители секретной информации; criminal proceeding; state secrets; material transmitters of secret information